A numerically efficient fuzzy MPC algorithm with fast generation of the control signal - Marusak, Piotr M. (Zielona Góra: Uniwersytet Zielonogórski)
Model predictive control (MPC) algorithms are widely used in practical applications. They are usually formulated as optimization problems. If a model used for prediction is linear (or linearized on-line), then the optimization problem is a standard, i.e., quadratic, one. Otherwise, it is a nonlinear, in general, nonconvex optimization problem. In the latter case, numerical problems may occur during solving this problem, and the time needed to calculate control signals cannot be determined. Therefore, approaches based on linear or linearized models are preferred in practical applications. A novel, fuzzy, numerically efficient MPC algorithm is proposed in the paper.
Keywords: model predictive control; fuzzy systems; fuzzy control; nonlinear control